Fuzzy Logic to Determine the Effect of Parental Attention and Peer Environment on Mathematics Learning Outcomes - Supratman; Andi Mariani Ramlan; Raden Sulaiman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The results of learning mathematics is a process of changing new behavior which is the result of giving experiences received by students in the learning process which includes cognitive, affective, and psychomotor aspects whose success can be measured through written and oral tests. The learning outcomes achieved can be good or bad depending on the factors that influence them, including learning motivation and environmental factors study. This study aims to determine the effect of parental attention and peer environment on student learning outcomes at SMA Negeri 1 Kolaka in 2022 using the Fuzzy logic of the Tsukamoto method. The data obtained in this study came from a questionnaire for the attention of parents and peers that had been filled out by students as well as mathematics learning outcomes obtained through the results of the even semester 2022 daily test scores. Based on the research results obtained in fuzzy calculations consisting of people's attention questionnaires parents and peer environment, it was found that the mathematics learning outcomes achieved were not good at 34.87 towards good mathematics learning outcomes at 65.12.